PENGARUH LEVERAGE DAN FIRM SIZE TERHADAP LUAS PENGUNGKAPAN SUKARELA (STUDI PADA PERUSAHAN MANUFAKTUR YANG LISTING DI BURSA EFEK INDONESIA PERIODE 2013 S.D 2015) - Ade Fitri Anggraeni; Makhdalena Makhdalena; Hardisem Syabrus (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2019)
Abstrack: This study aims to determine the effect of leverage and firm size on the extent of voluntary disclosure both simultaneously and partially in manufacturing companies listed on the Indonesia Stock Exchange for 2013 until 2015. The population oh this research is 18 manufacturing and textile companies. Company with a 3 year observation year in which the data is examined by census. This study uses secondary data sourced from financial statement. The data analysis tecnique used is multiple linier regression assisted by the statistical package social sciences program. The results showed that leverage and firm size had a simultaneous effect on the extent of voluntary disclosure, while partially leverage had a positive effect on the extent of voluntary disclosure and firm size had a negative effect on the extent of voluntary disclosure.Key Words: Leverage, Firm Size and Voluntary Disclosure.